Quality of medicines : deficiencies found by Brazilian Health Regulatory Agency (ANVISA) on good manufacturing practices international inspections - Geyer, Andrea Renata Cornelio (2018)
The circulation of poor quality medicines, especially in the developing countries, is a public health concern. Compliance with good manufacturing practices (GMP) is essential to ensure the quality, efficacy, and safety of medicines. This study evaluated the outcomes of the Brazilian Health Regulatory Agency's (ANVISA) international inspections of two years (2015 and 2016) and compared these to those of other regulatory authorities. The information from 255 inspection reports was analyzed, and the type and extent of deficiencies were collected. In the period evaluated, 62.75% of ANVISA-inspected companies were classified as GMP ªsatisfactory,º 24.71% were classified as having ªon demandº status, and 12.55% of inspections concluded that the company did not comply with Brazilian GMP regulations (ªunsatisfactoryº). The most common areas of deficiency were documentation (28.63%) and premises (26.27%). The pattern of deficiencies was similar to the findings of other regulatory agencies. However, ANVISA detected a more significant number of non-compliance results than other authorities, which may be caused by differences in classifications adopted by each Agency. Furthermore, manufacturers inspected by ANVISA may follow different standards and practices for products manufactured for the Brazilian market. Disclosure of main GMP deficiencies found can be useful for encouraging the industry to comply with GMP, and additional guidelines in the specific areas where deficiencies are often identified may be useful to industry to improve GMP compliance. Harmonization of GMP guidelines and inspection procedures are the key steps to avoid duplicate work, but regulatory authorities also need to work together to enforce the proper level of GMP compliance by pharmaceutical manufacturers, assuring high quality and safe medicines supply.